The Effect of Alkaline Activator Types on Strength and Microstructural Properties of Geopolymer from Co-Combustion Residuals of Bamboo and Kaolin - Aprilina Purbasari; Tjokorde Walmiki Samadhi; Yazid Bindar (Universitas Gadjah Mada, 2018)
Geopolymer as a Portland cement substitute had been synthesized from alkaline activation of co-combustion residuals of bamboo and kaolin. Types of used alkaline activators were NaOH solution, KOH solution, a mixture of NaOH solution-water glass, and a mixture of KOH solution-water glass. Geopolymer with NaOH solution as activator had a compressive strength which was higher compared to geopolymer with KOH solution as an activator. However, geopolymer with NaOH solution-water glass as activator had a compressive strength which was lower compared to geopolymer with KOH solution-water glass as activator either at room temperature curing or at a curing temperature of 60 °C. The use of water glass with NaOH or KOH solution as activator could increase the compressive strength of geopolymer and yielded geopolymer having more dense and more homogeneous microstructure seen from SEM images. XRD patterns revealed the presence of sodium aluminosilicate hydrate in geopolymer with NaOH solution and NaOH solution-water glass as activators, and potassium aluminosilicate hydrate in geopolymer with KOH solution and KOH solution-water glass as activators. Furthermore, FTIR spectra indicated asymmetrical vibration of Si(Al)-O at around 1008 cm-1 related to geopolymer product.